PENGARUH CAPITAL ADEQUACY RATIO (CAR), LOAN TO DEPOSIT RATIO (LDR) DAN NON PERFORMING LOAN (NPL) TERHADAP HARGA SAHAM DENGAN GOOD CORPORATE GOVERNANCE (GCG) SEBAGAI VARIABEL MODERASI - Christian Tejakusuma; Lucas Kahar; Yulius Christiawan (Business Accounting Review, 2021)
This study aims to determine whether CAR, LDR, and NPL have an influence on the Stock Price (HS). In addition, this study also aims to determine whether GCG moderates the relationship between CAR, LDR, and NPL on Stock Price (HS). This study was conducted on 34 companies in the banking sector listed on the Indonesia Stock Exchange (IDX) in 2015 - 2019. This study uses panel data multiple linear regression techniques. The results of data testing prove that the banking ratio CAR and LDR have no effect on stock prices (HS). Meanwhile, GCG moderates by strengthening the relationship between CAR and LDR with Stock Price (HS) and GCG moderates by weakening the relationship between NPL and Stock Price (HS). The results of the study are expected to be useful for shareholders to pay more attention to the influence of banking ratios and GCG as the influence of stock prices.